2022
DOI: 10.1037/rep0000459
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and wellbeing after spinal cord injury: Perceived stress and adaptation to disability as mediators.

Abstract: Purpose/Objective: Spinal cord injury (SCI) is a life-altering acquired disability. Understanding factors that contribute to adaption to disability and decreased SCI-related stress are critical to personal wellbeing and quality of life for SCI patients. Previous research suggests that forgiveness of others, self-forgiveness, and overall forgiveness are associated with psychological well-being in patients with other chronic illnesses. As such, dimensions of forgiveness may be relevant factors in restoring welln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
(106 reference statements)
0
0
0
Order By: Relevance
“…This indicates that an individual's ability to forgive is positively associated with their level of psychological well-being. This finding is consistent with several previous studies that have investigated the effectiveness of forgiveness and concluded that forgiveness not only provides relief and a fresh start in life, but also lowers levels of depression, anxiety, and stress while increasing psychological well-being (Cornish et al, 2022;Ekawardhani et al, 2019;Juwita & Kustanti, 2020;Wade et al, 2014). Individuals who are capable of forgiveness are not able to change the events that caused them harm, but forgiveness has been shown to enable people to adjust their perspectives, emotions, mental associations, and understanding of the meaning of unpleasant events.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that an individual's ability to forgive is positively associated with their level of psychological well-being. This finding is consistent with several previous studies that have investigated the effectiveness of forgiveness and concluded that forgiveness not only provides relief and a fresh start in life, but also lowers levels of depression, anxiety, and stress while increasing psychological well-being (Cornish et al, 2022;Ekawardhani et al, 2019;Juwita & Kustanti, 2020;Wade et al, 2014). Individuals who are capable of forgiveness are not able to change the events that caused them harm, but forgiveness has been shown to enable people to adjust their perspectives, emotions, mental associations, and understanding of the meaning of unpleasant events.…”
Section: Discussionsupporting
confidence: 93%
“…This study is unique in focusing on the adult experience of bullying, an area less researched than that related to adolescents (Juwita & Kustanti, 2020;Quintana-Orts et al, 2021;Shaver et al, 2022). Previous studies also focus solely on the association between forgiveness and psychological well-being (Cornish et al, 2022;Ekawardhani et al, 2019) or spirituality and psychological well-being (Basileyo, 2019;Gireyhan, 2022). Therefore, the relationship between forgiveness, spirituality, and psychological well-being needs further exploration.…”
Section: Introductionmentioning
confidence: 99%